Social Perceptions About Community Life with People with Mental Illness: Study of a Discharge Program in Buenos Aires Province, Argentina - Ardila Gómez, Sara Elena (2015)
Effects of living near people with mental illness in community settings have been researched as part of psychiatric reform evaluation. However, these studies have been carried out mostly in industrialized countries, where social contexts differ from those in which psychiatric reform is now being implemented. To analyze the effects of community life with people with mental illness in the neighborhoods in which they live, in Buenos Aires, Argentina. A questionnaire was administered to randomly-selected neighbors of group homes of a discharge program and an equivalent control area (n = 236). Data was analyzed both quantitatively and qualitatively. Significant differences were found between being a neighbor and having a high degree of acceptance toward people with mental illness. In addition, significant associations were found between neighbors having a high-perceived social cohesion and having a high level of acceptance toward the mentally ill. Living near people with mental illness is associated with better acceptance toward them; these results are congruent with those results found in other cultural contexts.